The Impact of 12 Weeks of Moderate-Intensity Aerobic Exercise on Reducing Obesity in Older Adults - Kuswahyudi Kuswahyudi; Yasep Setiakarnawijaya; Bazzar Ari Mighra; Muhamad Syamsul Taufik; Yulingga Nanda Hanief (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2023)
Objective. Obesity is a significant health concern that can affect individuals of all ages, including children and adults. The purpose of this study is to evaluate the effectiveness of 12 weeks of moderate-intensity aerobic exercise in reducing complex obesity levels in older individuals. The research methodology used in this study is experimental, with a one-group pre-post test design. The study was conducted in June-July 2023 at the Jakarta State University Sports Hall, located in Rawamangun, East Jakarta. Following the participants' completion of 12 weeks of moderate-intensity aerobic exercise, a post-test was administered, which included measuring their BMI. Materials and Methods. The study involved 30 elderly participants who were obese. The sampling technique used was purposive sampling, with several criteria such as being male, aged between 55-65 years, having a body mass index (BMI) between 27-32 kg/m2, coming from a large family from the Faculty of Sports Science, Jakarta State University, and being willing to participate in research on the effects of moderate-intensity aerobic exercise for 12 weeks. The research aimed to determine the effects of moderate-intensity aerobic exercise for 12 weeks on reducing the level of complex obesity in elderly people. Result. The research findings indicate that the 12-week program of moderate-intensity aerobic exercise, designed by researchers, is an effective approach to significantly decrease complex obesity in the elderly population. The results of the study demonstrate the potential benefits of engaging in regular physical activity to improve the health and well-being of older adults. Conclusion. The study results indicate that engaging in aerobic exercise of moderate intensity, such as running on a treadmill, for 12 weeks can lead to a significant decrease in body fat and weight, thus promoting effective obesity reduction.